Investigating Principals’ Knowledge and Perceptions of Second Language Programs for English Language Learners - Yolanda Padron; Hersh Waxman (International Journal of Educational Leadership and Management, 2016)
This study examined principals’ knowledge and perceptions of second language programs for English language learners (ELLs) operating in their schools. An open-ended survey and in-depth interviews were used to examine elementary school principals’ knowledge of the second language programs implemented at their schools. The survey asked principals about the strengths and challenges accompanying the program model currently implemented in their school(s), both anticipated and unanticipated of the program, and the staffing and professional development needed to improve the program. The interview asked similar questions to those on the survey and additional questions about the specific second language program(s) operating in their schools. Results indicated that principals had very limited knowledge about how the second language program(s) operating in their schools. Generally, principals attributed the success of their second language programs to the teachers in the program. The lack of knowledge about how to properly implement second language program is of concern since it is important for principals to be instructional leaders in their schools. Knowing how teachers should implement second language programs appropriately can assist principals in providing support to teachers as well as determining the type of training that their teachers may need in working more effectively with second language students.